Caminhos do saber local à agroecologia: escolhas e mudanças de práticas agrícolas nos assentamentos da reforma agrária de Iperó/SP - Silva, Josefa Erica Monteiro da (Universidade Federal de São Carlos, 2021)
SILVA, Josefa Erica Monteiro da. Paths of the local knowledge to Agroecology: choices and practice changes at Settlings of Iperó’s Land Reform. 2021. Monograph. (Bachelor Degree in Biological) – Universidade Federal de São Carlos campus Sorocaba, Sorocaba, 2021. Agroecology emerges as a critical science to the hegemonic model, and proposes the multidimensionality of sustainability for the development of ecological agriculture. As a practice, it proposes innovative technologies, which are consistent with the peculiarities of different realities and respects the ecology of knowledge. In addition to that, it works as well as a socio-cultural and political movement, related to the demands of local people and communities that exist and resist daily. Ecological agriculture presupposes that, instead of fighting symptomatic factors and replacing chemical products with organic ones, as in organic agriculture for instance, there is a holistic view of the agroecosystem in order to deal with causal factors. The importance of the Agroecological Transition process lies in the resignification of the management of agroecosystems, moving away from the model based on the use of agrochemicals and transgenics to the construction of principles that aim at a healthier relationship with nature. In this context, the present work analyzes the role of local knowledge on choices and changes in agricultural practices throughout the history of the Ipanema and Horto Bela Vista (Iperó/SP) settlements, towards agroecological practices, in order to understand how it occurs the construction of knowledge, which factors influenced the choices of agricultural practices and the effect of the latter on the lives of farmers. For this matter, semi-structured interviews were carried out with the farming families involved in the Participatory Guarantee System (SPG) and, therefore, already practicing sustainable management (but not necessarily agroecological). Results pointed to a vast knowledge about agroecological and agricultural practices, such as agrobiodiversity, use of organic matter in the farms, intercropping and crop rotation, little use of machinery and ecological management of the soil. This knowledge is linked to the involvement of farmers in exchanges from the SPG, experiences in the field, transmission between generations and sociocultural awareness, but mainly in the horizontality and dialogue of knowledge between farmers, extension workers and the “Rede Agroecológica Sorocabana”, which contributes to the construction of agroecological knowledge, confidence and self-esteem of the settlers. Among the factors that influenced the agroecological transition are reports of intoxication due to the use of pesticides, socio-environmental awareness, consumer demand, financial motivation, access to knowledge, public policies and agroecological transition projects. As for the effects of these choices on the lives of farmers, there is an increase in the possibilities of disposal, quality of life, financial security and food sovereignty, based on an analysis that encompasses an ecological, socioeconomic, cultural, political and ethical view.
Paths of the local knowledge to Agroecology: choices and practice changes at Settlings of Iperó’s Land Reform.
Keywords: Práticas agroecológicas; MST; Transição agroecológica; Construção do conhecimento; Agroecological practices; Agroecological transition; Knowledge construction; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL